ELIMINATION BY SUBSTITUTION: CHRIST APOSTOLIC CHURCH AND INDIGENOUS FAITH INTERPLAY IN NIGERIA - Ogunleye, A. Richard (European Scientific Journal, ESJ, 2013)
This article explores the unique method of ‘elimination of substitution’ often use by the Christ Apostolic Church (CAC) in its bid to eradicate indigenous worship among the Yoruba people in Nigeria. It is particularly concerned to show how the Christ Apostolic Church, an independent Pentecostal church, has transformed Nigerian Christianity from a cold and Eurocentric to a dynamic and power demonstrating one. In spite of the various challenges that the church is facing, the CAC reveals the deep spirituality and great concern for practical and existential issues through its holistic presentation of Jesus as savior, healer, and deliverer. The paper concludes that, the CAC is a blessing for Nigeria in the sense that it brings many souls to Christ through its services to God and humanity.